Mast cells distribution and variations in epithelium thickness and basement membrane in oral lichen planus lesion and oral lichenoid reaction - Gholamreza Jahanshahi; Parichehr Ghalayani; Laleh Maleki (Wolters Kluwer Medknow Publications, 2012)
Background: Oral lichen planus (OLP) is a chronic mucocutaneous lesion with unknown etiology. Oral lichenoid lesions (OLL) comprise a family of lesions with different etiologies. Both lesions have similar clinical and histopathologic characteristics although their management is different. Differential diagnosis between OLP and OLL has always been a major challenge. Materials and Methods: In this prospective analytical study, the role of mast cells in pathogenesis of these lesions was investigated by evaluation of 52 patients with clinical and histopathological diagnosis of OLP (26 cases) and OLL (26 cases) based on WHO criteria, and by applying a more accessible staining methods, Hematoxylin and Eosin, toluidine blue (histochemistry) and Periodic Acid Schiff staining. In order to distinguish these two lesions, number of mast cells and thickness of epithelium and basement membrane were measured using light microscopy. Data were analyzed by SPSS software using t-test method (P<0.001). Results: No significant difference was observed between the total numbers of mast cells of two groups (P=0.148), but a statistically significant difference was detected between degranulated mast cells in two groups (P<0.001). A significant difference was also observed between the thickness of epithelium in two groups (P<0.001), although no difference was seen between basement membrane thickness in these lesions. Conclusion: Number of degranulated mast cells in reticular layer of corium in lichenoid lesions was more than that of OLP. This implies that despite the increase in number of these cells, in both groups of diseases, the role of these cells has not been the same in pathogenesis of the diseases. Moreover, the epithelium thickness was lower in lesions of OLP compared to lesions of oral lichenoid, so this parameter may be a useful criterion together with other histopathological and clinical finding to discriminate these lesions. However, discrepancy of basement membrane thickness can not be a reliable criterion. Finally we suggest more accessible staining methods which are reliable for differentiation of these two lesions.